Pengaruh Tinggi dan Berat Badan Pengemudi terhadap Kenyamanan Ergonomi Mobil Listrik 2 KW Barata Berdasarkan Metode RULA - Andre Setiawan; Asroful Abidin; Mokh. Hairul Bahri (Lembaga Pengembangan Kinerja Dosen, 2026)
The BARATA 2 kW electric car is a compact electric vehicle developed to support energy efficiency and research activities. The limited cabin space in this vehicle has the potential to affect driver comfort due to differences in anthropometric characteristics, particularly height and weight. This study aims to analyze the influence of driver height and weight on ergonomic comfort in the 2 kW BARATA electric car using the Rapid Upper Limb Assessment (RULA) method. The study involved 30 participants, with data collected on height, weight, elbow angle, and knee angle. The anthropometric data were used to model the driver’s posture in CATIA V5 software, followed by an ergonomic analysis using the RULA method and statistical testing using SPSS. The results showed that 80% of the respondents obtained RULA scores in the 3–4 range, which falls into the category requiring further investigation, while 20% of the respondents obtained scores of 5–6, indicating the need for posture improvement. Partial test results showed that height did not have a significant effect on the RULA score with a significance value of 0.815, while body weight had a significant effect with a significance value of 0.000. In addition, the results of the simultaneous test indicate that height and weight together have a significant effect on the driver’s ergonomic comfort. Thus, the cabin design of the 2 kW BARATA electric car has been able to accommodate most drivers, but still requires refinement to improve the user’s ergonomic comfort